Benchmarking in Educational Organizations - Demirkol, Murat; Karagözoğlu, Ahmet Alper; Çelik, Yunus (Kahramanmaraş İstiklal Üniversitesi, 2023)
In order to survive, public and private sector organizations must be aware that the expectations of service recipients are rising with increasing competition and that their work must be carefully scrutinized. Considering these reasons, in order to meet the increasing demands, institutions need to find new techniques that will enable them to show that they perform their jobs well and to increase the value of the business economically, in order to be at the forefront of the competition. Educational institutions are also involved in this competitive process. In this context, educational institutions need to develop tools that can be embedded into their structures that enable them to learn from both their own successes and failures, as well as from the best practices of others. The comparison method can be used to perform these operations. In this context, the concept of benchmarking and its importance in the field of education are discussed in the study. As a result of this study, which was conducted as a compilation research, benchmarking for educational institutions was seen as an effective tool that not only evaluates internal performances but also enables learning from best practices in the sector. It has been concluded that institutions that adopt this strategy for continuous development and innovation can provide more effective service to students.

Kamu ve özel sektör örgütleri, hayatlarını sürdürebilmek için, artan rekabetle birlikte hizmet alanların beklentilerinin yükseldiğinin ve işlerinin ince elenip sık dokunması gerektiğinin farkında olmak zorundadır. Bu sebepler göz önünde bulundurularak, artan talepleri karşılayabilmek için, kurumların, rekabette ön sıralarda olmak adına, işlerini iyi ifa ettiklerini göstermeleri ve ekonomik olarak işin değerini yükseltmelerini sağlayacak yeni teknikler bulmaları gerekmektedir. Eğitim kurumları da bu rekabet süreci içinde yer almaktadır. Bu bağlamda eğitim kurumlarının hem kendi başarıları hem de başarısızlıklarından ve aynı zamanda başkalarının en iyi uygulamalarından öğrenmelerini sağlayan kendi yapılarına yerleştirilebilecek araçlar geliştirmeleri gerekmektedir. Bu işlemleri yapabilmek için kıyaslama metodu kullanılabilir. Bu kapsamda çalışmada kıyaslama kavramı ve eğitim alanındaki önemi ele alınmıştır. Derleme araştırması olarak gerçekleştirilen bu çalışma sonucunda, eğitim kurumları için kıyaslama, sadece içsel performansları değerlendirmekle kalmayıp aynı zamanda sektördeki en iyi uygulamalardan öğrenmeyi sağlayan etkili bir araç olarak görülmüş. Sürekli gelişim ve yenilik için bu stratejiyi benimseyen kurumların, öğrencilere daha etkin hizmet sunabileceği sonucuna varılmıştır.
Eğitim Örgütlerinde Kıyaslama
Keywords: Social Development; Sosyal Gelişim